Nghiên cứu các yếu tố ảnh hưởng đến ý định mua mỹ phẩm thuần chay của người tiêu dùng thế hệ Z - Châu Thị Lệ, Duyên; Huỳnh Chí Thảo, Vy; Đồng Thị Bảo, Trâm; Nguyễn Gia Bảo, Duy; Võ Trung, Tín; Nguyễn Trần Anh, Hào (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Research shows that Generation Z is a generation with good environmental awareness, the choice of vegan cosmetics when researched on Gen Z customers is in line with new consumption trends. The study used regression analysis to show that factors such as attitude, perceived behavioral control, environmental awareness, emotional value, and functional value (price) have positive relationships with purchase intention. vegan cosmetics of Generation Z consumers. Among these factors, Functional Value has the strongest influence on the intention to purchase vegan cosmetics, followed by Attitude and Environmental Awareness In the environment, the two factors Emotional value and Perceived behavioral control have a negligible impact. Therefore, businesses operating in the vegan cosmetics industry should focus on factors such as Functional Values, Attitudes, and Environmental Awareness to have more appropriate and effective business strategies.